2015
DOI: 10.1111/joim.12378
|View full text |Cite
|
Sign up to set email alerts
|

No association between adherence to the healthy Nordic food index and cardiovascular disease amongst Swedish women: a cohort study

Abstract: The present results do not support an association between a healthy Nordic food index and risk of cardiovascular disease in Swedish women. There was also no effect modification by alcohol intake, BMI or age. Our finding of an interaction with smoking status requires reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 43 publications
(58 reference statements)
2
39
1
5
Order By: Relevance
“…As discussed by the authors, failure to properly account for wholegrain intake could explain the lack of an association between whole-grain intake and cardiovascular disease and potentially also the lack of an association with the entire index. 10 Evidence from cohort studies suggest that a high intake of whole grains is associated with a lower risk of stroke, and our analyses of the individual Healthy Nordic Food Index items also indicated that oatmeal and rye bread are important components. 27 Adherence to a healthy Nordic diet may affect the risk of stroke through several mechanisms.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…As discussed by the authors, failure to properly account for wholegrain intake could explain the lack of an association between whole-grain intake and cardiovascular disease and potentially also the lack of an association with the entire index. 10 Evidence from cohort studies suggest that a high intake of whole grains is associated with a lower risk of stroke, and our analyses of the individual Healthy Nordic Food Index items also indicated that oatmeal and rye bread are important components. 27 Adherence to a healthy Nordic diet may affect the risk of stroke through several mechanisms.…”
Section: Discussionmentioning
confidence: 55%
“…20 In contrast to our results, no association between adherence to the Healthy Nordic Food Index and risk of stroke was reposted in a cohort study among Swedish women. 10 To adapt the Healthy Nordic Food Index to the FFQ used in their cohort, the authors included whole-grain bread instead of rye bread. Further, whole-grain crisp bread, which is expected to be a major source of whole grains in the Swedish population, could not be separated from nonwhole-grain crisp bread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six key Nordic foods formed the basis of the healthy Nordic food index, which was associated with an 18% lower total mortality between the highest and lowest diet scores over 21 years in Swedish women [96] . However, the diet was not associated with CVD risk in the same cohort [97] . In a Danish cohort, greater adherence to the healthy Nordic index was associated with a 25% lower risk of type 2 diabetes over 15 years in women and a 38% lower risk in men [98] .…”
Section: Translating Dietary Recommendations To Food-based Guidelinesmentioning
confidence: 77%
“…Allerdings basieren die bisherigen Daten auf kleinen Untersuchungen, die nur über einen kurzen Zeitraum von einigen Wochen oder Monaten durchgeführt wurden. Weitere Studien im Hinblick auf klinische Endpunkte erscheinen notwendig, zumal aktuelle Ergebnisse einer schwedischen Kohorte keine Assoziation zwischen der NORDIC Diet und kardiovaskulären Ereignissen detektieren konnte[18].…”
unclassified